Improvement of a Lightweight Aluminium Cylinder Block Design Using Finite Element Stress Analysis - Arsah, Mohamad A; Syed Mohd Yusoff Sobbry, Syed M A; Tuan Kamaruddin, Tengku Nordayana Akma; Osman, Azmi (International Journal of Integrated Engineering, 2020)
A SAE technical paper (2012-01-0406) has discussed about the design and manufacturing method of a lightweight cylinder block made from cast iron. In applying the features discussed in the paper to an aluminium cylinder block with a different displacement, certain modifications need to be made to the previously proposed design. In addition to that and following the ongoing trend, many modern engines have a boosting system thus necessitating the engines to be designed to withstand a higher peak combustion pressure. The mentioned SAE paper has a proven design for a 2-liter cylinder block, but the maximum peak cylinder pressure is only about 85 bar representing the naturally-aspirated engine. Thus, the new proposed design simulating a boosted engine with maximum pressure up to 120 bar requires modifications to be made especially to the critical fasteners in terms of the bolt designs, engaged thread and the structural reinforcements of the bolt bosses. The cylinder block was modelled using CATIA V5 software and stress analysis of the baseline and proposed designs were done using the same software to analyse the critical area and force distribution. Two main areas have been investigated which are near cylinder head bolt thread area and near crankshaft bearing cap thread area. It was found that, the alterations manage to increase the factor of safety and eliminating the concentrated force at certain locations. The design modifications made can improve the factor of safety by decreasing the stress and adding more structural strength focusing on cylinder head bolt threaded area and crankshaft bearing cap thread area.